Effects of periplocoside T isolated from Periploca sepium on behavior and sensory-CNS-motor circuits in Drosophila melanogaster larvae. - Zuo, Y.; Ren, Y.; Pei, Y.; Aioub, A.A.A.; Hu, Z. (Pesticide Biochemistry and Physiology, 2023)
Periplocoside T (PST) from Periploca sepium has insecticidal activity against some lepidopterans, which can significantly inhibit the activity of vacuolar-type H[+]-ATPases (V-ATPase). V-ATPase is involved in the release of neurotransmitters in vesicles during nerve signal transduction. However, there are actions of PST on behavior and sensory-central nervous system (CNS)-motor neural circuit which are commonly overlooked. After exposure to 500 mg/L PST for 48 h, the difference of the proportion of larvae responding to stimuli in the four Drosophila strains was not significant as compared to controls, but larval mouth hook movement and body wall motion were significantly decreased as compared to controls, and the decrease was more obvious in para[ts1]; DSC1[-/-] and DSC1[-/-] strains, especially in para[ts1]; DSC1[-/-] strain. Compared with control (DMSO), the excitatory junction potential (EJP) frequencies of sensory-CNS-motor circuits in the four Drosophila strains after PST or bafiloymcin A1 (BA1, a V-ATPase specific inhibitor) treatment gradually decreased with time, and the decreasing amplitude of BA1 treatment was greater than that of PST treatment, but both were higher than that of the control. The decay amplitude of EJP frequency in two strains with DSC1 channel knockout was lower than that of w[1118] and para[ts1] strains without DSC1 channel knockout. Thus, the results indicated that PST, similar to BA1, could inhibit the transmission of sensory-CNS-motor circuit excitability of Drosophila larvae by inhibiting the activity of V-ATPase, and DSC1 channel play a role of in regulating the stability of nervous system.